Demonstration of Forward Collision Avoidance Algorithm Based on V2V Communication - Hosny, Ahmed; Yousef, Mohamed; Gamil, Wessam; Adel, Mohamed; Mostafa, Hassan; Darweesh, M. Saeed (2019 8th International Conference on Modern Circuits and Systems Technologies (MOCAST), 2019)
This paper proposes a hardware implementation of a Vehicle-to-Vehicle (V2V) communication-based forward collision avoidance algorithm by alarming the driver about potential crashes. The proposed system benefits from the information exchange between the host vehicle and the leading vehicle to calculate the safe distance between the host vehicle and leading vehicle to guarantee the avoidance of the collision. The proposed system gives advisory and imminent warnings according to the predicted accident levels, using three different levels of collision avoidance. This work tests a prototype implementation of a complete V2V communication, designed according to the Basic Safety Message (BSM) specification SAE J2735. The purpose of this work is to prove the feasibility of V2V to improve the safety of transportation systems. The results show that the proposed collision avoidance system makes a composite analysis of the collision risk and provides an accurate real-time warning.